Hubungan Romantic Relationship Satisfaction dengan Perilaku Phubbing pada Orang Tua - Rahmawati, Gustina; Yasmin, Maya (Lembaga Yasin AlSys, 2025)
The rapid advancement of technology has led to increased gadget use in daily life, including among parents. While technology facilitates access to information, negative impacts such as phubbing, the tendency to ignore people nearby due to excessive focus on gadgets are increasingly evident, particularly in parent-child interactions. One factor suspected to contribute to this behavior is low romantic relationship satisfaction between partners. This study aims to examine the relationship between romantic relationship satisfaction and phubbing behavior among parents in West Sumatra. A quantitative approach was employed, involving 410 mothers with children aged ≤12 years, selected through purposive sampling. The research instruments were developed based on the phubbing theory by Karadağ et al. (2015) and the romantic relationship satisfaction framework by Hendrick (1988). Pearson correlation analysis revealed a significant negative relationship between romantic relationship satisfaction and phubbing behavior (r = -0.361; p < 0.05). These findings indicate that the higher the satisfaction in a romantic relationship, the lower the tendency of parents to engage in phubbing toward their children. The study concludes that the quality of romantic relationships within the family plays a crucial role as a preventive strategy to reduce phubbing and improve parenting quality in the digital age.